2013
DOI: 10.1016/j.heares.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous 3D imaging of sound-induced motions of the tympanic membrane and middle ear ossicles

Abstract: Efficient transfer of sound by the middle ear ossicles is essential for hearing. Various pathologies can impede the transmission of sound and thereby cause conductive hearing loss. Differential diagnosis of ossicular disorders can be challenging since the ossicles are normally hidden behind the tympanic membrane (TM). Here we describe the use of a technique termed optical coherence tomography (OCT) vibrography to view the sound-induced motion of the TM and ossicles simultaneously. With this method, we were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
(46 reference statements)
2
34
1
Order By: Relevance
“…The measured sensitivity of the instrument was 0.5nm (calculated for an SNR = 10). This correlate well with sensitivities reported by other groups: 4.8 mrad, reported by Chang et al [20] and 7.5 mrad, reported by Subhash et al [22].…”
Section: Instrument Optimizationsupporting
confidence: 93%
See 1 more Smart Citation
“…The measured sensitivity of the instrument was 0.5nm (calculated for an SNR = 10). This correlate well with sensitivities reported by other groups: 4.8 mrad, reported by Chang et al [20] and 7.5 mrad, reported by Subhash et al [22].…”
Section: Instrument Optimizationsupporting
confidence: 93%
“…A pilot study with a handheld OCT scanner has been recently reported [18], where the thickness of the TM was investigated as a diagnostic indicator for otitis media [19]. However, the functional characteristics of the middle ear structures cannot be analyzed with conventional OCT. A newer variant of OCT, called phase-sensitive OCT, has been used by some research groups both in animal models, such as mice and chinchillas, to measure the vibration of the middle ear TM and the ossicles [20], as well as to assess the functionality of the inner ear (e.g. the cochlea) [21].…”
Section: Introductionmentioning
confidence: 99%
“…First, one must correct for phase jitter caused by wavelength instability inherent to swept-laser sources and asynchrony between the source and sample clocks (22), as both factors impede measurement of subnanometer displacements. Using a phase reference from a nonvibrating structure within the scan can work in some situations (23). However, we completely eliminated phase jitter by calibrating the spectral interferograms every sweep using the phase of the Hilbert transform of the spectral interferograms from a Mach-Zehnder interferometer with a fixed optical delay that were simultaneously acquired.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial profile of corneal vibration was determined by using the principle of vibrography previously described [19,20]. Briefly, at a constant sound frequency the optical beam was scanned along a line (~10 mm) or over an area.…”
Section: Experimental Methodsmentioning
confidence: 99%